CBME framework to promote transition to senior - Acker, Amy; Leifso, Kirk; Hawksby, Emily (Canadian Medical Education Journal, 2020)
Residency programs across Canada are transitioning to Competence by Design (CBD). Our innovative framework improves the traditional transition to independent senior overnight call process by adding workplace-based (WBA) assessments. Our process ensures that faculty and residents have a shared understanding of what competencies need to be demonstrated before residents can work independently as the in-house senior resident overnight. This protocol is worth exploring; initial perceptions suggest an increase in resident confidence while on call and improved faculty comfort when paired with these senior residents. We believe that this in turn will be reflected in enhanced patient care.